The economic determinants of fertility: Three decades of evidence from the Philippines - Enriquez, Hannah J.; Cidro, Analiza C.; Ignacio, Aldrin John J.; Silvestre, Mary Rose S. 4 0 16; 5
u
Research Paper: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2021
Keywords: 2 -- 0; 6; 20; 20; 2